Maternal Morbidity in Patients With Morbidly Adherent Placenta Treated With and Without a Standardized Multidisciplinary Approach. Issue 1 (March 2016) - Shamshirsaz, A.A.; Fox, K.A.; Salmanian, B.; Diaz-Arrastia, C.R.; Lee, W.; Baker, B.W.; Ballas, J.; Chen, Q.; Van Veen, T.R.; Javadian, P.; Sangi-Haghpeykar, H.; Zacharias, N.; et al.
Abstract : ( Am J Obstet Gynecol. 2015;212:218.e1-218.e9) Placenta accreta is a significant cause of postpartum hemorrhage and is associated with a 40% risk for massive blood transfusion, as well as a 6% to 7% chance of death. This condition results from the myometrium being invaded by the placenta so that manual attempts to remove it from the uterine wall lead to hemorrhage. The authors of this study attempted to determine whether maternal morbidity in this condition could be reduced through the application of a standardized multidisciplinary approach for patients with a morbidly adherent placenta.